ANALISIS PENGARUH TOTAL ASET DAN LIABILITAS ASURANSI TERHADAP SOLVABILITAS ASURANSI SYARIAH DI INDONESIA: Indonesia - Annisa Ayu, Kayla; Fajrin, Nabila; Algifari, Salman; Arya Aditya, Mochammad (Benefits : Jurnal Ekonomi dan Pariwisata Internasional, 2025)
The problem in this research is the imbalance between total assets and total liabilities, which can affect the solvency level of Islamic insurance companies in Indonesia. This study aims to analyze the influence of total assets and total liabilities on the solvency of Islamic insurance companies in Indonesia. The research approach used is quantitative with panel data regression analysis method, utilizing secondary data from the financial statements of four Islamic insurance companies during the period from the first quarter of 2018 to the fourth quarter of 2022. The research results indicate that total assets have a positive and significant impact on solvency levels, while total liabilities have a negative and significant impact. This finding indicates the importance of effective management of assets and liabilities to maintain the company's financial health. This research suggests that companies increase investment in productive assets and manage liabilities carefully, and recommends exploring other factors that could affect solvency in the future.